Cross-Cultural Responsiveness & Systemic Therapy Personal & Clinical Narratives (Focused Issues in Family Therapy, 2018)
This progressive volume takes a nuanced approach to understanding systemic therapies with diverse client populations, leading to culturally responsive therapy. Synthesizing diverse streams of psychology, philosophy, and social theory, chapters focus on cutting-edge issues in couple and family therapy including social justice, power, and privilege in therapy, the role of evidence-based practices, and integrative approaches to couple and family therapy. Each contributor is either a recent immigrant to the U.S. or a person of color, bringing unique personal lenses and experiences to the exploration of the topics. And coverage also makes clear what white therapists need to learn-and unlearn-before they can work responsively with clients of color. This practice-building reference: Combines research with applied knowledge in its treatment of topics. Adapts systemic therapy practice into today's culturally diverse contexts. Explores themes of power, privilege, and social justice in each chapter. Presents multiculturalism in terms of therapeutic responsiveness. Critiques approaches to systemic therapy with immigrant clients and clients of color. Challenges readers to access deeper concepts and realities of self, other, and trust. Updating familiar takes on cultural competence with both local and global implications, Cross-Cultural Responsiveness and Systemic Therapy describes numerous opportunities for and challenges to couple and family therapy, as well as cross-disciplinary opportunities for incorporating social justice and cultural responsiveness in training and supervision of couple and family therapists.